Hiatal hernia recurrence after open surgery - a systematic review regarding risk factors - Ana Carolina Domingues de Oliveira Rodrigues Amarante (2021)
Introduction Due to fragility of phrenoesophageal membrane and nearby structures such as diaphragmatic crura (among other causes), hiatal hernias can develop. This results in intrathoracic migration of a portion of the digestive tube through the esophageal hiatus, with added risk of complications such as reflux, esophagitis, or even strangulation. This surgical repair can be performed traditionally with open surgery or, more recently, by minimal invasive surgery. The factors that determine hiatal hernia recurrence after open repair are not yet well understood. Methods Following the PRISMA guidelines, we performed a systematic review of literature regarding risk factors for recurrence after open surgery for hiatal hernia repair. We used both Medline and Scopus libraries. Results We identified a total of 1070 records. After exclusion of duplicates, unavailable and non-relevant articles, we included 18 studies in our qualitative analysis. Discussion Several studies consider the role of acute presentation, higher patient BMI, older age, or the type of surgery with or without a reflux procedure. However, a lack of significant association between these factors and a higher recurrence risk remains. A significant association was found between serious reflux complications the risk of recurrence, in one study. There is also a lack of consensus regarding what constitutes a recurrence, and how to diagnose it. Conclusion The factors related to the recurrence of hiatal hernia after open repair remain controversial. There is a need for prospective studies that allow for a more comprehensive understanding specially with better evidence on why hernias recur and how can this be prevented.